Application of Backstepping to the Virtual Flux Direct Power Control of Five-Level Three-Phase Shunt Active Power Filter - Bouzidi Mansour; Bouafia Saber; Bouzidi Ali Ali; Benaissa Abdelkader; Barkat Said (Institute of Advanced Engineering and Science, 2014)
This paper proposes a virtual flux direct power control-space vector modulation combined with backstepping control for three-phase five-level neutral point clamped shunt active power filter. The main goal of the proposed active filtering system is to eliminate the unwanted harmonics and compensate fundamental reactive power drawn from the nonlinear loads. In this study, the voltage-balancing control of four split dc capacitors of the five-level active ﬁlter is achieved using five-level space vector modulation with balancing strategy based on the effective use of the redundant switching states of the inverter voltage vectors. The obtained results showed that, the proposed multilevel shunt active power filter with backstepping control can produce a sinusoidal supply current with low harmonic distortion and in phase with the line voltage.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5621